Approach to Assessment of Risk Factors in Mild Hypertension. Issue 5912 (27th April 1974) - Stuart, K. L.; Desai, Patricia; Lalsingh, Adella
Abstract : Criteria are urgently needed for the early detection of subjects with only mildly raised blood pressure who may be at high risk of developing the complications of hypertension. As a step towards the establishment of such criteria we have examined the association of certain possible "risk" factors—namely, x-ray evidence of cardiac enlargement, high serum cholesterol levels, effort pain, E.C.G. abnormalities, and high systolic blood pressure—with fatal or morbid endpoints in a five-year follow-up study of subjects whose diastolic pressure had been found initially to be between 95 and 114 mm Hg. The index group consisted of 22 patients in whom these end-points occurred. They comprised death from cardiovascular disease, clinical or E.C.G. deterioration, and either an increase in diastolic pressure of at least 10 mm Hg or a diastolic pressure of 115 mm Hg or both. The control group consisted of 22 subjects chosen at random from other respondents with the same range of diastolic pressures and the same age and sex distribution. "Any two or more" of the possible risk factors examined were found to occur significantly more often in the index group than in the controls, suggesting a possible approach to the early detection of high-risk subjects. The value of longterm studies along these lines and the urgent need for them are emphasized.